HER2-positive breast cancer with invasive micropapillary carcinoma component shows immunosuppressive microenvironment and resistance to neoadjuvant therapy - Zhang, Lulu; Zhou, Lijia; Yang, Anli; Zheng, Shaoquan; Chen, Keming; Zou, Yutian; Zhou, Qingru; Wang, Daining; Xu, Fei; Huang, Jiajia; Yuan, Zhongyu; Wang, Shusen; et al. (Frontiers in Immunology, 2025)
BackgroundInvasive micropapillary carcinoma (IMPC) is a rare histopathological subtype of breast cancer (BC) that shows a high incidence of human epidermal growth factor receptor 2 (HER2)-positive expression. However, the therapeutic efficacy of current standard anti-HER2 therapies for this distinct BC subtype remains unclear.MethodsWe retrospectively analyzed patients with HER2-positive BC who underwent neoadjuvant therapy with trastuzumab (H) or trastuzumab plus pertuzumab (HP) between 2015 and 2023 at Sun Yat-sen University Cancer Center. On the basis of the presence of an IMPC component in pretreatment tumor samples, patients were stratified into IMPC and non-IMPC groups. Baseline clinical and pathological characteristics, pathological complete response (pCR) rates, and survival outcomes were compared between two groups. Additionally, gene expression profiles and immune cells infiltration were assessed using GSE66418 dataset obtained from the Gene Expression Omnibus and ImmuCellAI databases. To validate bioinformatics findings, matched pretreatment tumor samples from both groups were analyzed.ResultsAmong the 244 patients included in the study, 38 had an IMPC component (IMPC group), whereas 206 did not (non-IMPC group). The IMPC group exhibited significantly lower pCR rates compared to the non-IMPC group: 21.6% vs. 47.1% (P = 0.004) overall, 15.0% vs. 28.4% (P = 0.223) in the H-based subgroup, and 27.8% vs. 57.6% (P = 0.017) in the HP-based subgroup. IMPC patients also showed worse disease-free survival (P < 0.001) and overall survival (P = 0.0482) than non-IMPC patients. Bioinformatics analysis revealed that the CTNNB1 gene, which encodes the β-catenin protein, was the most highly upregulated gene in IMPC patients. Immune profiling demonstrated reduced infiltration of CD4+ and CD8+ T cells, along with increased macrophage levels in the IMPC tumor microenvironment (TME). Further validation using matched tumor samples confirmed decreased levels of tumor-infiltrating lymphocytes, CD4+ and CD8+ T cells, elevated M2 macrophages, and higher programmed death-ligand 1 (PD-L1) expression in the IMPC group.ConclusionHER2-positive BC with IMPC demonstrates intrinsic resistance to anti-HER2 neoadjuvant therapy and harbors an immunosuppressive TME. These findings highlight the need for alternative treatment strategies and warrant prospective validation.